2003
DOI: 10.1038/nm916
|View full text |Cite
|
Sign up to set email alerts
|

Clonal vaccinia virus grown in cell culture as a new smallpox vaccine

Abstract: Although the smallpox virus was eradicated over 20 years ago, its potential release through bioterrorism has generated renewed interest in vaccination. To develop a modern smallpox vaccine, we have adapted vaccinia virus that was derived from the existing Dryvax vaccine for growth in a human diploid cell line. We characterized six cloned and one uncloned vaccine candidates. One clone, designated ACAM1000, was chosen for development based on its comparability to Dryvax when tested in mice, rabbits and monkeys f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 18 publications
1
121
1
1
Order By: Relevance
“…In the present study, the monkeys were infected with MPXV by either the intranasal or the subcutaneous route in order to design an appropriate nonhuman-primate model not only for MPX but also for variola. The symptoms associated with MPX in naïve monkeys challenged intranasally with MPXV were somewhat milder than those reported in previous studies (15,37,39). This may have been due to the differences in MPXV strains, infection routes, or virus doses used for challenge.…”
Section: Discussioncontrasting
confidence: 53%
“…In the present study, the monkeys were infected with MPXV by either the intranasal or the subcutaneous route in order to design an appropriate nonhuman-primate model not only for MPX but also for variola. The symptoms associated with MPX in naïve monkeys challenged intranasally with MPXV were somewhat milder than those reported in previous studies (15,37,39). This may have been due to the differences in MPXV strains, infection routes, or virus doses used for challenge.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, a vaccine regimen incorporating peptides may also be utilized in a prime-and-boost strategy to reduce side effects from the present vaccines, especially in immunocompromised individuals. Some recent studies have utilized attenuated viruses for this purpose, either alone or as part of a prime-boost regimen, in monkeys (19) and humans (61).…”
Section: Discussionmentioning
confidence: 99%
“…This is an ankyrin-Fbox-containing protein of unknown function and a homolog of the variola virus (Bangladesh) B18R gene. Moreover, in a previous study, a similar DVX_213-encoding strain, called CL3, was shown to be the most virulent clone among six different Dryvax-derived isolates (51). We wondered if DVX_213 might be a virulence factor and tested it by inserting a yellow fluorescent protein (YFP)-GTP cassette into the DVX_213 locus in DPP25.…”
Section: Figmentioning
confidence: 99%